Belatacept for renal rescue in lung transplant patients. (8th February 2016) - Timofte, Irina; Terrin, Michael; Barr, Erik; Sanchez, Pablo; Kim, June; Reed, Robert; Britt, Edward; Ravichandran, Bharath; Rajagopal, Keshava; Griffith, Bartley; Pham, Si; Pierson, Richard N.; et al.
Summary: Renal failure causes morbidity and mortality after lung transplantation and is aggravated by exposure to nephrotoxic immunosuppressant (IS) drugs. We report an off‐label experience using belatacept for lung transplant recipients with severe renal insufficiency to reduce nephrotoxic IS exposure. We analyzed data retrospectively from a consecutive series of lung transplant patients with renal insufficiency in whom belatacept treatment was initiated between June 2012 and June 2014 at the University of Maryland Medical Center. Eight patients received belatacept because of acute or chronic renal insufficiency (median) GFR 24 (IQR 18–26). Glomerular filtration rate (GFR) remained stable in two patients and increased in five. One patient with established renal and respiratory failure received only the induction dose of belatacept and died 4 months later of respiratory and multisystem organ failure. Calcineurin inhibitor or sirolimus exposure was safely withheld or reduced without moderate or severe acute rejection during ongoing belatacept in the other seven patients. FEV1 remained stable over the 6‐month study interval. Belatacept use appears to permit safe transient reduction in conventional immunosuppressive therapy and was associated with stable or improved renal function in a small retrospective series of lung transplant recipients with acute or chronic renal insufficiency.